The effects of group cohesion on the productivity of advisory groups that plan employee training programs in a university setting - Robert P. Wislock (Adult Education Research Conference, 1995)
Advisory groups are one important method that adult educators can use to plan programs. This study’s purpose was to determine if a relationship existed between group cohesiveness and productivity in advisory groups that plan training programs. The major finding indicated that there was a significant relationship between these two variables.